Evaluation of Bone Metabolism in Children Using Antiseizure Drugs: A Single-Center Experience and Review of the Literature - Tekin, Emine; Gül, Ülkü Şiraz; Aydın, Sultan Köker; Köksoy, Adem Yasin (Journal of Pediatric Epilepsy, 2022)
The effect of anti-seizure drugs (ASDs) on bone mineral density (BMD) is a controversial topic. This study investigated the effect of monotherapy and polytherapy drugs separately. Patients with a history of epilepsy treated with the same ASDs for more than 6 months were included in the study. Data regarding patient demographics, biochemical markers related to bone metabolism (calcium, phosphorus, alkaline phosphatase, parathyroid hormone, vitamin D), and BMD with dual-energy X-ray absorptiometry (DXA) were collected and compared. In total, 104 children with epilepsy using valproic acid (VPA), levetiracetam (LEV), carbamazepine (CBZ) alone or in combination and 22 healthy controls were evaluated. The ages of the children (64 boys, 62 girls) ranged between 2 and 17, with a mean of 9.50 ± 4.03 years. BMD or Z-scores did not differ among the monotherapy groups or between them and the polytherapy group. The lowest mean Z-score was in the VPA group but without statistical significance. Alkaline phosphatase levels were significantly higher in the group using CBZ. Calcium levels significantly differed between the groups (p = 0.001). The CBZ and LEV groups had the lowest calcium levels. However, phosphorus and vitamin D measurements did not significantly differ by ASDs used. Unfortunately, low vitamin D levels were evident in all children with epilepsy and even among controls. Physical activity, sun exposure, and calcium intake might be recommended in children treated with ACDs and in combination with additional risk factors monitoring via DXA should be considered. Further studies in a large population are necessary to judge which ASDs are more at risk to reduce bone mineralization than others.
Keywords: bone mineralization; bone mineral density; dual-energy X-ray absorptiometry; epilepsy; vitamin D